Effect of Flavones Extracted from Lavender Flowers Against Some Bacteria that Cause Food Poisoning - Abdul Elah Muhmmed, Suadad; Noory Ali, Inaam; Khalel Farhan, Rasha; Nazar Baqer, Loay; Muhmmed Kadem, Eman (Al-Nahrain Journal of Science, 2024)
The lavender plant is a shrub-shaped plant. It contains many active substances such as volatile oils, terpenes, and flavonides are considered antioxidants, antibacterial and antifungal substances. Take up the research extract and detect for flavonoids in the flowers of the lavender plant, especially the anthocyanin pigment, due to its important demand. The dried alcoholic extract (flavonoids) was prepared at different concentrations, estimated in milligrams per milliliter (mg/ml). And to study its effect on the bacteria Staphylococcus aureus and the bacteria Bacillus cereus that cause food poisoning, the active ingredient (flavonoids) was detected using ethyl alcohol and the base potassium hydroxide (KOH) at a concentration of 50%. The reagent was added to the aqueous extract of lavender flowers, and a yellow-brown color appeared indicating a positive detection. Then the extraction process was carried out using ethyl alcohol at a concentration of 80% to obtain the pure extract containing the anthocyanin dye. The anthocyanin pigment was identified using HPLC device compared with the standard solution. The active substance appeared at a retention time of 2 minutes. Then prepare a series of half-dilutions of the dried extract from the original concentration of 800mg/ml. For the purpose of testing the sensitivity of staphylococcus and bacillus bacteria to the plant extract using the wells method, and measuring the diameter of the inhibition zone mm. The results indicate that it is in the inhibition zone for Staphylococcus bacteria, it is 17 mm at a concentration of 800 mg/ml which is minimum bactericidal concentration (MBC) value, and the lowest inhibition zone is 12 mm at a concentration of 400 mg/ml, which is the value of the minimum inhibitory concentration (MIC). As for Bacillus bacteria, its highest zone of inhibition was 22 mm at a concentration of 800 mg/ml which is minimum bactericidal concentration (MBC) value, and its lowest zone of inhibition was 15 mm at a concentration of 200 mg/ml. which is its MIC value. . This result encourages the use of anthocyanin pigment as a preservative in food due to its being an inhibitor of the bacteria that cause food poisoning.